NiCrAl structured catalyst and preparation and application methods thereof

By growing NiCrAl-LDHs nanosheet arrays in situ on the surface of metal substrates, the problem of large-scale generation of catalytic materials in solution in hydrothermal method is solved, and the catalyst is highly active, stable and low-cost preparation is achieved.

CN119500167APending Publication Date: 2025-02-25INST OF ELECTRICAL ENG CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411703677.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When the existing hydrothermal method prepares structured catalysts, the catalytic material is generated in large quantities in the solution, resulting in waste of materials and unstable catalyst performance.

Method used

The metal substrate in the aqueous urea solution is used as the metal source, and the NiCrAl-LDHs nanosheet array is grown in situ on the surface of the metal substrate through hydrothermal reaction, avoiding uncontrolled precipitation of metal salts in the solution.

Benefits of technology

The high activity and stability of the catalyst are achieved, and the problems of waste of materials and poor catalyst performance are avoided. At the same time, the preparation process is simplified and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500167A_ABST
    Figure CN119500167A_ABST
Patent Text Reader

Abstract

The invention discloses a NiCrAl structured catalyst as well as a preparation method and an application method thereof. The catalyst contains NiCrAl layered double hydroxides (NiCrAl-LDHs) and a metal substrate, the NiCrAl-LDHs vertically grow on the surface of the metal substrate in situ, nickel ions, chromium ions and aluminum ions in the NiCrAl-LDHs structure come from the metal substrate, and the preparation method comprises the following steps: dissolving urea in water to prepare a urea aqueous solution; and putting the metal substrate into the urea aqueous solution, and carrying out hydrothermal reaction to obtain the composite material. The application method of the catalyst comprises the following steps: introducing current into the catalyst in a reaction atmosphere, and driving the catalytic reaction by using Joule heat generated by the current. The NiCrAl structured catalyst provided by the invention has the characteristics of simple preparation method, less chemical reagent dosage, excellent catalytic performance, easiness in batch production and the like, and is very suitable for application of electrothermal catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysis, and particularly relates to a NiCrAl structured catalyst and a preparation and application method thereof. Background Art

[0002] Unlike traditional particulate catalysts, structured catalysts have a macroscopic continuous skeleton matrix, which has many advantages, such as facilitating precise design of the reactor flow field and the catalyst surrounding environment, enhancing heat / mass transfer in the reaction process, reducing bed pressure drop and improving catalyst utilization efficiency. They are receiving increasing attention in fields such as heterogeneous catalysis and reactor engineering.

[0003] The continuous skeleton matrix of the structured catalyst can be made of materials such as metal and ceramic. Due to the easy processing, good thermal conductivity and mechanical properties of metal materials, the development and application of metal-based structured catalysts with metal materials as continuous skeleton matrix have attracted much attention. In particular, in recent years, the "resistance internal heating" catalytic method has emerged, which uses the continuous skeleton matrix of the structured catalyst as a conductive path and uses the Joule heat generated by the current inside to drive the reaction. This has brought new opportunities for the development of structured catalysts. In particular, electric heating metals have the characteristics of high electric heat conversion efficiency, good resistance stability, high temperature resistance and corrosion resistance. Structured catalysts prepared as skeleton substrates are ideal objects for application under the "resistance internal heating" method.

[0004] The preparation of metal-based structured catalysts requires catalytic functionalization technology on the surface of the metal substrate, which can be mainly divided into coating technology and non-coating technology. Coating technology often has problems such as the difference in thermal expansion coefficient between the catalyst coating and the metal substrate, which can easily lead to cracking and peeling of the coating, and the stress effect caused by the irregular edges and corners of the substrate skeleton, which leads to poor coating uniformity and easy cracking of the coating. These problems will be more prominent under the "resistance internal heating" reaction mode. Non-coating metal surface in-situ catalytic functionalization technology is an important strategy to solve the above problems.

[0005] The hydrothermal method is a non-coated metal surface in-situ catalytic functionalization technology. The general hydrothermal method is to place the metal substrate in an aqueous solution containing a metal salt for hydrothermal treatment, use the metal salt as the metal source, and grow a metal-containing catalytic material in situ on the surface of the metal substrate. For example: in patent CN104226330B, a foamed nickel substrate is placed in an aqueous solution containing a soluble cobalt salt for hydrothermal treatment, and a cobalt hydroxide thin film micron sheet with a sheet-like morphology is grown on its surface; in patent CN102343283B, an aluminum substrate is placed in a solution containing divalent metal ions for hydrothermal treatment, and a binary hydrotalcite film is grown on its surface. An important problem with this preparation method is that during the hydrothermal reaction, the metal-containing catalytic material is not only generated on the surface of the metal substrate, but also generated in large quantities in the solution, which will not only form a large amount of precipitation and cause waste of materials, but also there will be a problem of random deposition of the catalytic material formed in the solution on the metal substrate, which will not only affect the uniformity of the reaction temperature when the structured catalyst is used in the "resistance internal heating" reaction mode, but also easily fall off and cause unstable catalyst performance. Summary of the invention

[0006] The purpose of the present invention is to provide a NiCrAl structured catalyst and a preparation and application method thereof. The catalyst is a NiCrAl structured catalyst with high activity, high stability, simple preparation and suitable for "resistance internal heating" application.

[0007] A first aspect of the present invention provides a NiCrAl structured catalyst, which contains NiCrAl layered double hydroxides (NiCrAl-LDHs) and a metal substrate, wherein the NiCrAl-LDHs grows vertically in situ on the surface of the metal substrate, the surface of the metal substrate contains nickel, chromium and aluminum elements, and the nickel ions, chromium ions and aluminum ions in the NiCrAl-LDHs structure come from the metal substrate.

[0008] Preferably, the metal substrate is a nickel-chromium-aluminum alloy substrate. Preferably, based on the total mass of the nickel-chromium-aluminum alloy substrate, the nickel-chromium-aluminum alloy substrate contains: Ni 60-85wt%, Cr 5-25wt% and Al 1-16wt%. For example, based on the total mass of the nickel-chromium-aluminum alloy substrate, the nickel-chromium-aluminum alloy substrate contains: Ni 60wt%, 65wt%, 70wt%, 75wt%, 80wt% or 85wt%; Cr 5wt%, 10wt%, 15wt%, 16.8wt%, 20wt% or 25wt%; Al 1wt%, 5wt%, 8.2wt%, 10wt%, 15wt% or 16wt%.

[0009] Optionally, the metal substrate has a morphological structure of foam, fiber, wire, wire mesh, tube or sheet.

[0010] Preferably, the NiCrAl-LDHs have a sheet thickness of 0.5 to 20 nm (e.g., 0.5 nm, 5 nm, 10 nm, 15 nm or 20 nm), and are in close contact and staggered arrangement on the surface of the metal substrate to form a two-dimensional nanosheet array morphology with an open porous structure.

[0011] The second aspect of the present invention provides a method for preparing the above-mentioned NiCrAl structured catalyst, comprising the following steps: dissolving urea in water to prepare a urea aqueous solution; placing a metal substrate having nickel, chromium and aluminum on its surface into the urea aqueous solution, and preparing the NiCrAl structured catalyst through a hydrothermal reaction.

[0012] Optionally, the concentration of urea in the urea solution is 0.5 mmol / L to 10 mol / L. For example, the concentration of urea in the urea solution is 0.5 mmol / L, 50 mmol / L, 100 mmol / L, 150 mmol / L, 200 mmol / L, 250 mmol / L, 300 mmol / L, 400 mmol / L, 500 mmol / L, 600 mmol / L, 700 mmol / L, 800 mmol / L, 900 mmol / L, 1000 mmol / L, 3 mol / L, 6 mol / L, 9 mol / L or 10 mol / L.

[0013] Preferably, the concentration of urea in the urea solution is 0.5 mmol / L to 1 mol / L.

[0014] Preferably, the temperature of the hydrothermal reaction is 50-300°C (e.g., 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 200°C, 250°C or 300°C). The time of the hydrothermal reaction is 2-16 hours (e.g., 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 14 hours or 16 hours). During the reaction, under the etching of urea, nickel ions, chromium ions and aluminum ions are dissolved from the surface of the metal substrate while the NiCrAl-LDHs sheet structure is in situ grown on the metal surface. The change in urea concentration can regulate the size, thickness and other structural parameters of the NiCrAl-LDHs sheet.

[0015] Preferably, after the hydrothermal reaction is completed, the product is cooled naturally to room temperature and then washed and dried.

[0016] Preferably, the metal substrate is pretreated with an acid solution before being added to the reaction kettle to remove the oxide layer and organic residues on the metal surface.

[0017] Preferably, the acid solution is a hydrochloric acid solution, a sulfuric acid solution or a nitric acid solution.

[0018] Preferably, the pretreatment operation may be: immersing the metal substrate in the acid solution, ethanol and water in sequence for ultrasonic washing, and then drying.

[0019] Preferably, the NiCrAl structured catalyst is calcined in a reducing atmosphere containing hydrogen before being used in the catalytic reaction, and the calcination temperature is 200-900°C, for example, the calcination temperature is 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C.

[0020] Specifically, the calcined NiCrAl structured catalyst is placed in a reactor, heated to 200-900°C (e.g., 750°C) at a rate of 1-10°C / min (e.g., 1°C / min, 3°C / min, 4°C / min, 6°C / min, 8°C / min or 10°C / min) in a reducing atmosphere containing hydrogen and maintained for 1-8 hours (e.g., 4 hours), then naturally cooled to room temperature and taken out for use.

[0021] The third aspect of the present invention provides an application method of the NiCrAl structured catalyst, wherein an electric current is passed through the NiCrAl structured catalyst in a reaction atmosphere, and the Joule heat generated by the electric current is used to drive the catalytic reaction.

[0022] The technical solution of the present invention has the following advantages: (1) The present invention uses a metal substrate to provide a metal source for the growth of metal catalytic materials, so that the hydrothermal reaction only occurs on the surface of the metal substrate. This can effectively avoid the problem of relying on metal salts in the solution to provide a metal source and forming a large amount of uncontrollable and ineffective precipitation in general hydrothermal methods. It not only avoids material waste, but also prevents the problems of uneven active components and easy detachment caused by random precipitation, such as poor catalyst performance.

[0023] (2) The present invention can prepare an ultra-thin and uniform two-dimensional LDHs nanosheet array structure on the surface of a metal substrate, which can form highly dispersed and highly stable nano-metal catalytic active sites supported by a composite metal oxide after calcination under the action of lattice confinement, and its open porous array structure can expose a large number of catalytic active sites, thereby having good catalytic performance.

[0024] (3) The present invention requires fewer types of chemical reagents and no metal salts need to be added to the solution. Only urea can be used to uniformly grow NiCrAl nanocatalytic materials on the surface of the metal substrate in situ, and the amount of urea used can be very small. The method is not only simple, but also low in cost, green and environmentally friendly, and easy to mass produce.

[0025] (4) The present invention enables the NiCrAl nanocatalytic material to be directly grown in situ on the metal substrate, which not only has no effect on the conductivity of the metal substrate, but also ensures that the connection between the catalytic active sites and the metal substrate is tight, firm and uniform, is not easy to fall off at high temperatures, and has good structural stability.

[0026] (5) The present invention can in-situ grow high-performance nano-catalytic materials on the surface of electrothermal alloys containing metal atoms such as nickel, chromium and aluminum, and can easily form a composite carrier with excellent resistance heating performance and catalytic performance. It is very suitable for the application of the "resistance internal heating" method that uses the Joule heat of electric current to drive the catalytic reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 is a scanning electron microscope image of the NiCrAl-LDHs prepared in Example 1; Figure 2 is the X-ray photoelectron spectrum of NiCrAl-LDHs prepared in Example 1; Figure 3 is a scanning electron microscope image of NiCrAl-LDHs prepared in Example 2. DETAILED DESCRIPTION

[0028] The present invention provides a NiCrAl structured catalyst which is prepared by a hydrothermal method, uses a metal substrate as a metal source, uses urea as an etchant and a precipitant, and in-situ grows a NiCrAl-LDHs nanosheet array on the surface of the metal substrate. The NiCrAl structured catalyst can be used directly as a catalyst or as a precursor after reduction and calcination.

[0029] The NiCrAl structured catalyst has a conductive and high-temperature resistant metal substrate and can be used both under power-on conditions and under high-temperature conditions.

[0030] The NiCrAl structured catalyst uses an in-situ chemical reaction strategy to complete the catalytic functionalization of the metal substrate surface. Its preparation is independent of the macroscopic morphological structure of the metal substrate. In specific implementation, a variety of metal substrates such as foam, fiber, wire, wire mesh, tube, sheet, etc. can be used.

[0031] The nickel, chromium and aluminum elements in the NiCrAl-LDHs all come from the surface of the metal substrate, and the ratio of nickel, chromium and aluminum elements in the two has a certain correlation. 2+) and trivalent metal ions (Al 3+ and Cr 3+ ) can be adjusted, and the ratio between the two trivalent metal ions (Al 3+ and Cr 3+ ) can also be adjusted. In specific implementation, there is no need to strictly limit the ratio of nickel, chromium and aluminum elements in the metal substrate. Generally, the mass percentage of nickel, chromium and aluminum elements in the metal substrate should not be less than 0.5%.

[0032] Embodiment 1: (1) Pretreatment of metal substrate: A 70 mm × 3.8 mm × 1 mm NiCrAl foam metal (the mass percentage of each metal element determined by inductively coupled plasma atomic emission spectrometry is Ni: 75%, Cr: 16.8%, Al: 8.2%) is first immersed in a dilute hydrochloric acid solution (2 mol / L) and placed in an ultrasonic cleaner for 5 minutes, then cleaned with anhydrous ethanol and deionized water in turn, and then placed in a forced air drying oven at 65°C for 3 hours and taken out for use.

[0033] (2) Hydrothermal reaction: Weigh 1.2g of urea and dissolve it in 80ml of water to prepare a 250mmol / L urea aqueous solution, then transfer it into a high-pressure reactor, place the pretreated NiCrAl foam metal in step (1) into the reactor and immerse it in the urea solution, seal the reactor and place it in an oven for heating, keep it at 110°C for 8 hours, and then cool it naturally to room temperature. Take out the NiCrAl structured catalyst and wash it with anhydrous ethanol and deionized water in turn, and place it in a forced air drying oven at 65°C for 12 hours. The scanning electron microscope (SEM) photo and X-ray photoelectron spectroscopy (XPS) diagram of the prepared NiCrAl structured catalyst are shown in Figure 1 and Figure 2 . Figure 1 It shows that after the hydrothermal reaction, a vertically grown, tightly interlaced two-dimensional nanosheet array structure is formed on the surface of the NiCrAl metal substrate. The thickness of the two-dimensional nanosheet layer is about 10-20nm. Figure 2 It shows that this nanoarray structure is mainly composed of elements such as Ni, Cr and Al.

[0034] Embodiment 2: (1) Metal substrate pretreatment: the same as step (1) of Example 1.

[0035] (2) Hydrothermal reaction: 0.06 g of urea was weighed and dissolved in 80 ml of water to prepare a 12.5 mmol / L urea aqueous solution. The rest of the process was the same as step (1) of Example 1. The scanning electron microscope (SEM) photograph of the prepared NiCrAl structured catalyst is shown in Figure 3 . Figure 3It shows that after the hydrothermal reaction, an in-situ grown, interlaced two-dimensional nanosheet array structure is formed on the surface of the NiCrAl metal substrate. The thickness of the two-dimensional nanosheet layer is about 10 nm, and the distribution density is sparser than that in Example 1, indicating that urea concentration is an important factor affecting the growth of the nanosheet layer.

[0036] Application Example 1: (1) Reduction Calcination: The NiCrAl structured catalyst in Example 1 was placed in a ceramic boat and placed in a tubular furnace. A hydrogen-argon mixed gas (volume ratio of 1:9) was introduced and the temperature was raised to 750°C at a rate of 4°C / min and maintained for 4 hours. After naturally cooling to room temperature, the catalyst was taken out for use.

[0037] (2) Installing copper terminals and wires: Copper terminals are clamped on both ends of the NiCrAl structured catalyst that has been subjected to reduction and calcination treatment, and a copper wire is connected to each copper terminal.

[0038] (3) Application of methane dry reforming reaction under the “resistance internal heating” mode: The reaction raw materials are methane, carbon dioxide and argon (molar ratio is 2:2:3). The NiCrAl structured catalyst equipped with copper wires is placed in a quartz tube reactor. The two wires are led out of the reactor and connected to the positive and negative terminals of the power supply respectively under the premise of ensuring airtightness. The reaction raw materials are introduced into the reactor at a flow rate of 30 ml / min. The NiCrAl structured catalyst is heated by electricity. The reaction products are analyzed by a thermal conductivity cell detector. The conversion rates of methane and carbon dioxide under different currents are listed in Table 1.

[0039] Table 1 Effect of the applied current size under the “resistance internal heating” mode on the catalytic activity of the NiCrAl structured catalyst prepared in Example 1 for methane dry reforming reaction Table 1

[0040]

[0041] Application Example 2: (1) Reduction calcination: The NiCrAl structured catalyst in Example 2 was used, and the rest was the same as step (1) in Application Example 1.

[0042] (2) Install copper terminals and wires: Same as step (2) in Application Example 1.

[0043] (3) Application of methane dry reforming reaction under "resistance internal heating" mode: The same as step (3) in Application Example 1, the conversion rates of methane and carbon dioxide under different currents are listed in Table 2.

[0044] Table 2 Effect of the applied current size under the "resistance internal heating" mode on the catalytic activity of the NiCrAl structured catalyst prepared in Example 2 for methane dry reforming reaction Table 2

[0045]

[0046] The present invention is not limited to the above-mentioned implementation modes, and any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A NiCrAl structured catalyst, characterized in that: The catalyst contains NiCrAl layered double hydroxides (NiCrAl-LDHs) and a metal substrate. The NiCrAl-LDHs grows vertically in situ on the surface of the metal substrate. The surface of the metal substrate contains nickel, chromium and aluminum elements. The nickel ions, chromium ions and aluminum ions in the NiCrAl-LDHs structure come from the metal substrate.

2. The catalyst according to claim 1, characterized in that The metal substrate is a nickel-chromium-aluminum alloy substrate; preferably, the morphological structure of the metal substrate is foam, fiber, wire, wire mesh, tube or sheet.

3. The catalyst according to claim 1, characterized in that The NiCrAl structured catalyst is calcined in a reducing atmosphere containing hydrogen before being used in a catalytic reaction.

4. The catalyst according to claim 1, characterized in that The NiCrAl-LDHs have a sheet thickness of 0.5 to 20 nm, are in close contact with each other and are arranged in a staggered manner on the surface of the metal substrate, and form a two-dimensional nanosheet array morphology with an open porous structure.

5. The method for preparing the NiCrAl structured catalyst according to any one of claims 1 to 4, characterized in that: The steps include: (1) Dissolving urea in water to prepare a urea aqueous solution; (2) placing a metal substrate containing nickel, chromium and aluminum on its surface into the urea aqueous solution, and preparing the NiCrAl structured catalyst through a hydrothermal reaction; The prepared NiCrAl structured catalyst contains NiCrAl layered double metal hydroxides (NiCrAl-LDHs) and the metal substrate, and the NiCrAl-LDHs are in-situ vertically grown on the surface of the metal substrate.

6. The method according to claim 5, characterized in that In step (1), the concentration of urea in the urea aqueous solution is 0.5 mmol / L to 10 mol / L.

7. The method according to claim 5, characterized in that In step (2), the metal substrate is a nickel-chromium-aluminum alloy substrate.

8. The method according to claim 5, characterized in that In step (2), before adding the urea aqueous solution, the metal substrate is pretreated with an acid solution to remove the oxide layer and organic residues on the metal surface.

9. The method according to claim 5, characterized in that The acid solution is a hydrochloric acid solution, a sulfuric acid solution or a nitric acid solution.

10. The application method of the NiCrAl structured catalyst according to claim 1, characterized in that: An electric current is passed through the NiCrAl structured catalyst in a reaction atmosphere, and the Joule heat generated by the electric current is used to drive the catalytic reaction.

Citation Information

Patent Citations

  • Vertically aligned layered double hydroxides (LDHs) film and application thereof in structured catalysis

    CN102343283B

  • A kind of au / co(oh) 2 Nanoarray Structured Catalysts

    CN104226330B

Cited By

  • Electric internal heating Pt / CeO2 / Foam monolithic catalyst, preparation method thereof and methyl cyclohexane dehydrogenation method

    CN122124787A

  • Pt / TiO2 / Foam structured catalyst, preparation method thereof and method for catalyzing dehydrogenation of methylcyclohexane by electric internal heating

    CN122424831A